The potential of kyllinga erecta Schumach and Cyperus rotundus Linn. to remediate soil contaminated with heavy metals from used engine oil in Cameroon - Fontem Lum, A.; Chikoye, David (Informa UK Limited, 2018)
Contaminated soils are a serious environmental problem in developing countries. Poor disposal of used engine oil from vehicles is a source of soil contamination in Buea, Cameroon. This study was conducted in the University of Buea Teaching and Research Farm to determine the ability of two sedges (Kyllinga erecta Schumach and Cyperus rotundus Linn.) to remediate crop land contaminated with used engine oil. The experiment consisted of the two sedges and the following used oil levels (v/wt): 0, 5, 10, 20, 40 and 60 ml/kg of soil. Control treatments with 0 and 60 ml of used engine oil/kg of soil without the sedges were also included. The plant (roots and shoots) and soil samples were analyzed for heavy metal contents using the Inductively Coupled Plasma Optical Mass Spectrometry analytical package for ultra-low detection and high precision. The root and shoot dry biomass of both sedges decreased with an increase in soil contamination. Cyperus rotundus accumulated high concentrations of Cr (mean = 64.8 ± 19.5 ppm) and Cd (mean =1.2 ± 0.2 ppm) in its roots. Kyllinga erecta had the potential to extract Sn, Cd, Mn, Sr and Mo on soils contaminated with used oil at 60 ml/kg. Cyperus rotundus had phytostabilisation potential for Cd at concentrations of used oil ≤20 ml/kg and Rb at 20 ml/kg. The sedge also had phytoextraction potential for Cr and Rb on soils contaminated with used oil at concentrations up to 20 ml/kg. Therefore, the use of indigenous plants adapted to tropical environments could be a possible option for the sustainable remediation of soils contaminated with heavy metals from used engine oil.